The highlander's christmas bride ebook - Kelly, Vanessa (Clan Kendrick, 2019)
In bestselling author Vanessa Kelly's irresistible Clan Kendrick series, Christmas in the Highlands means family, celebration—and for one brother, the beginning of a passionate adventure . . .   Being thrown over by the man she expected to marry was humiliating enough. Now that Donella Haddon, grandniece of the Earl of Riddick, has also proven a failure as a nun, she has no choice but to return to her family's estate. The brawny Highlander sent to escort her is brash, handsome, and the only thing standing between Donella and a gang of would-be kidnappers. But the scandal in her past can't be so easily outrun . . .   Wealthy widower Logan Kendrick was expecting to meet a plain, pious spinster—not a gorgeous, sharp-tongued lass who can hold her own in any ambush. Though she's known as the Flower of Clan Graham, Donella is no shrinking violet. In fact, she might be the perfect woman to bring happiness back to his lonely little son's life, just in time for Christmas. But first he must protect her from ugly gossip and a mysterious threat—and convince her that their wild, unexpected desire is heaven sent.     Praise for The Highlander's Princess Bride   "A thoroughly satisfying Regency romance." — Publishers Weekly